Mitigation of paclitaxel-induced peripheral neuropathy in breast cancer patients using limb-cooling apparatus: a study protocol for a randomized controlled trial - Funasaka, Chikako; Hanai, Akiko; Zenda, Sadamoto; Mori, Keita; Fukui, Makoto; Hirano, Nami; Shinohara, Rie; Fuse, Nozomu; Wakabayashi, Masashi; Itagaki, Mai; Tomioka, Yutaka; Nishina, Michihiko; et al. (Frontiers in Oncology, 2023)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most common adverse events that can significantly impair the quality of life of patients. Although limb cooling may be beneficial for preventing CIPN, logistical challenges exist in ensuring consistent efficacy and safety. The purpose of this randomized controlled trial is to validate whether limb cooling with strict temperature control can reduce CIPN in patients with breast cancer receiving weekly paclitaxel as a perioperative treatment.Methods: This study is a multicenter, double-blinded, randomized controlled trial. We plan to enroll patients with breast cancer who are scheduled to receive 12 weekly doses of paclitaxel (60 min 80 mg/m 2 intravenous infusion) as perioperative chemotherapy. Patients will be randomly divided into the intervention or control groups and undergo limb cooling therapy maintained at a constant temperature of 13 °C and 25 °C, respectively. The primary endpoint is the proportion of patients who report Patient Neurotoxicity Questionnaire (PNQ) ≥ D in their limbs by the end of the study treatment or at the time of discontinuation.The results of this trial will contribute to the establishment of new evidence for limb cooling therapy in the mitigation of CIPN and present a safe and stable cooling device that may be suitable for use in the clinic.This trial has been registered with the Japan Registry of Clinical Trials (registration number: jRCT2032210115) and can be accessed at https://jrct.niph.go.jp/en-latestdetail/jRCT2032210115.